A Study on Two Distinguished Culture by Poets’ on ‘Nature’ - Dutta, Tinni (International Journal of Culture and History, 2023)
The concept of culture is the characteristic way of behaving and believing that a group of people in a country or region have evolved over time. Thus a people’s culture gives them a sense of who they are, provides them the capacity to adapt to circumstances, affect their emotion and lives. In human history, nature attraction and land cultivation are merged from the perspectives of culture. Natural beauty attracts the poets and they spontaneously reflect it in their writings. It is applicable for both the poets of east & west, especially in Romantic arena. They each require different psychological adaptations and transformations- needs, wishes, conflicts, anxieties and defenses. Wordsworth, Coleridge, Blake, Keats, Datta and Tagore beautifully mingle nature’s beauty and sooth human sufferings. We, the human beings, identify with them and feel beauty and joy from our unconscious and are able to transform our owes and pain. They are the symbols of unique cultural identity.